2018
DOI: 10.1101/290957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing roles of endosomal innate immunity proteins IFITM3 and TLR7 in human metapneumovirus infection

Abstract: Human metapneumovirus (hMPV) utilizes a bifurcated cellular entry strategy, fusing either with the plasma membrane or, after endocytosis, with the endosome membrane. Whether cellular factors restrict or enhance either entry pathway is largely unknown. We found that the interferon-induced transmembrane protein 3 (IFITM3) inhibits hMPV infection to an extent similar to endocytosis-inhibiting drugs, and an IFITM3 variant that accumulates at the plasma membrane in addition to its endosome localization provided inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Mice treated with amphotericin B experience more severe influenza virus infections, similar to IFITM3 KO mice [ 69 ]. We recently determined that IFITM3 is the first known restriction factor for human metapneumovirus infection, and we confirmed that amphotericin B completely neutralizes the antiviral activity of IFITM3 against both influenza virus and human metapneumovirus [ 22 ]. Thus, it will be interesting and important to determine whether clinical use of amphotericin B has the unintended consequence of increasing susceptibility to or pathogenicity of these and other virus infections due to its neutralizing effects on IFITM3.…”
Section: Remaining Questionsmentioning
confidence: 73%
See 3 more Smart Citations
“…Mice treated with amphotericin B experience more severe influenza virus infections, similar to IFITM3 KO mice [ 69 ]. We recently determined that IFITM3 is the first known restriction factor for human metapneumovirus infection, and we confirmed that amphotericin B completely neutralizes the antiviral activity of IFITM3 against both influenza virus and human metapneumovirus [ 22 ]. Thus, it will be interesting and important to determine whether clinical use of amphotericin B has the unintended consequence of increasing susceptibility to or pathogenicity of these and other virus infections due to its neutralizing effects on IFITM3.…”
Section: Remaining Questionsmentioning
confidence: 73%
“…Y20 phosphorylation is mediated by the Src family kinase Fyn and results in accumulation of IFITM3 at the plasma membrane and decreased antiviral activity against viruses, such as influenza virus, that enter cells through endocytosis and fuse with endosomes [ 24 , 25 ]. While phosphorylation may decrease IFITM3 activity against influenza virus, the altered localization enhances its ability to restrict certain viruses that fuse at the plasma membrane as mentioned above [ 18 , 21 , 22 ]. Phosphorylation of IFITM3 is dynamic, involving currently unidentified phosphatases [ 24 , 25 ].…”
Section: Ifitm3 Posttranslational Regulationmentioning
confidence: 99%
See 2 more Smart Citations